Advances in Stored Product Protection. Proceedings of the 8th International Working Conference on Stored Product Protection, Yo 2003
DOI: 10.1079/9780851996912.0827
|View full text |Cite
|
Sign up to set email alerts
|

The mortality of stored product insects following exposure to gaseous ozone at high concentrations.

Abstract: Ozone as a toxicant was evaluated against the stored product pests Plodia interpunctella and Tribolium confusum. Ozone was introduced into the continuous air stream flowing through a chamber made of high-density polyethylene and polycarbonate. By decreasing the flow of ozone and/or air in the chamber, various concentrations of ozone were obtained. The eggs, larvae and pupae were exposed to ozone at varying duration (1 to 18 h). The developmental stages exhibited delayed reactions to toxicity. Even high concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 0 publications
5
32
0
4
Order By: Relevance
“…The results presented by others show that eggs cannot be completely eradicated. For example, Leesch (2003) reported that high concentrations of ozone at 10.000 ppm for a 4-hour exposure time did not kill 100% of the eggs of P. interpunctella. Wood (2008) found eggs of the greater wax moth, Galleria mellonella L., to be more tolerant to ozone compared with larvae and adults.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented by others show that eggs cannot be completely eradicated. For example, Leesch (2003) reported that high concentrations of ozone at 10.000 ppm for a 4-hour exposure time did not kill 100% of the eggs of P. interpunctella. Wood (2008) found eggs of the greater wax moth, Galleria mellonella L., to be more tolerant to ozone compared with larvae and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Benzer şekilde ozon gazı ile ilgili daha önceden yürütülen çalışmalardan elde edilen sonuçlar toksisite sonuçları depolanmış ürün zararlısı türlerin ozon gazına karşı duyarlılıklarında önemli farklılıkların olduğunu göstermektedir (Leesch, 2003;Isikber & Oztekin, 2009;McDonough et al, 2011). Nitekim, Leesch (2003) T. confusum erginlerinin ozon gazına P. interpunctella erginlerine göre daha dayanıklı olduğunu bildirilmiştir. Benzer şekilde McDonough et al (2011) T. castaneum ve P. interpunctella'nın %100 ölümlerini elde etmek için gerekli olan konsantrasyon x uygulama süresi (C x t product) değerlerini heasplamışlar ve T. castaneum'un P. interpunctella'ya göre daha yüksek ozon konsantrasyonuna veya daha uzun ozon uygulama süresine ihtiyaç duyguklarını (sırasıyla 256,500 ppmdakika ve 183,000 ppm-dakika konsantrasyon x uygulama süresi (C x t product) değeri) bildirmişlerdir.…”
Section: Araştırma Sonuçları Ve Tartışmaunclassified
“…Erdman (1980) 45 ppm ozon konsantrasyonuna maruz bırakılan Tribolium confusum Jacquelin du Val ve T. castaneum'un erginlerinde yüksek ölümlerin gerçekleştiğini bildirmiştir. Leesch (2003) laboratuar koşullarında tek başına yüksek konsantrasyonda (300 ppm) ve kısa uygulama süresinde (4 saat) ozon gazı uygulamasının P. interpunctella' nın pupalarında yüksek oranda ölüme neden olduğunu bildirmiştir. Isikber & Öztekin (2009) iki depolanmış ürün zararlısı Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) ve T. confusum'un ozon gazına karşı duyarlılıklarını araştırmışlardır.…”
Section: Introductionunclassified
“…Rozado et al (2008) observed 95% mortality for adult maize weevil (MW) with 1,188 ppm-h and for adult red flour beetle (RFB) with 3,210 ppm-h. Pereira et al (2008) observed 95% mortality for adult RFB with 7,590 ppm-h at 20°C. Leesch (2002) observed 100% mortality for adult confused flour beetle (CFB) with 5,400 ppm-h, but also observed 100% mortality for adult Indian meal moth (IMM) with only 300 ppm-h. Similar results of 100% insect mortality with low ozone CTP at 292.5 ppm-h were also observed by Erdman (1980) for adult RFB and CFB.…”
mentioning
confidence: 99%
“…nsects and molds cause significant damage to grain each year producing economic losses that affect farmers, elevator managers, and processors throughout the world (Leesch, 2002). Stored grain protection relies heavily on the use of chemicals like methyl bromide and phosphine to control pests.…”
mentioning
confidence: 99%